A novel non invasive measurement of hemodynamic parameters: Comparison of single-chamber ventricular and dual-chamber pacemaker (Faculty of Medicine Universitas Indonesia, 2008)
We carried out a cross sectional study to analyze hemodynamic parameters of single-chamber ventricular pacemaker compared with dual-chamber pacemaker by using thoracic electrical bioimpedance monitoring method (Physio Flow™) - a novel simple non-invasive measurement. A total of 48 consecutive outpatients comprised of 27 single chamber pacemaker and 21 dual chamber were analyzed. We measured cardiac parameters: heart rate, stroke volume index, cardiac output index, estimated ejection fraction, end diastolic volume, early diastolic function ratio, thoracic fluid index, and systemic parameters: left cardiac work index and systemic vascular resistance index. Baseline characteristic and pacemaker indication were similar in both groups. Cardiac parameters assessment revealed no significant difference between single-chamber pacemaker and dual-chamber pacemaker in heart rate, stroke volume index, cardiac index, estimated ejection fraction, end-diastolic volume, thoracic fluid index. There was significantly higher early diastolic function ratio in single-chamber pacemaker compared to dual-chamber pacemaker: 92% (10.2-187.7%) vs. 100.6% (48.7-403.2%); p=0.006. Systemic parameters assessment revealed significantly higher left cardiac work index in single-chamber group than dual-chamber group 4.9 kg.m/m² (2.8-7.6 kg.m/m²) vs. 4.3 kg.m/m² (2.9-7.2 kg.m/m²); p=0.004. There was no significant difference on systemic vascular resistance in single-chamber compared to dual-chamber pacemaker. Single-chamber ventricular pacemaker provides similar stroke volume, cardiac output and left cardiac work, compared to dual-chamber pacemaker. A non-invasive hemodynamic measurement using thoracic electrical bioimpedance is feasible for permanent pacemaker outpatients. (Med J Indones 2008; 17: 25-32) Keywords: Permanent pacemaker, single chamber, dual chamber, thoracic electrical bioimpedance, hemodynamic parameter